2020
DOI: 10.1109/access.2020.3028621
|View full text |Cite
|
Sign up to set email alerts
|

V2X Support in 3GPP Specifications: From 4G to 5G and Beyond

Abstract: The connected car concept is gaining momentum from the point of view, not only of research, but also of standardization and industrial development. Today there are many options for connecting a vehicle, in terms of to whom and how. In addition to making use of any conventional cellular technology, and connecting the vehicle to a base station or infrastructure element, vehicles can connect wirelessly and directly to each other using different technologies, both from the Institute of Electrical and Electronics E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 17 publications
0
58
0
Order By: Relevance
“…The authors proposed an implicit acknowledgement method for improving packet delivery rate and developed a simulator named inventSim. Two main approaches for communication are DSRC by IEEE that supports vehicular ad-hoc WLAN technologies standardized as IEEE 802.11p and act as basis for European standard ETSI ITS-G5, and Cellular-based V2X (C-V2X), a proposal by the 3GPP, based on Long-Term Evolution (LTE), also known as LTE-V2X [31]. Recently, New Radio (NR) vehicle-to-everything has been specified in rel-16 standard of 3GPP based on 5G technology [32].…”
Section: Related Workmentioning
confidence: 99%
“…The authors proposed an implicit acknowledgement method for improving packet delivery rate and developed a simulator named inventSim. Two main approaches for communication are DSRC by IEEE that supports vehicular ad-hoc WLAN technologies standardized as IEEE 802.11p and act as basis for European standard ETSI ITS-G5, and Cellular-based V2X (C-V2X), a proposal by the 3GPP, based on Long-Term Evolution (LTE), also known as LTE-V2X [31]. Recently, New Radio (NR) vehicle-to-everything has been specified in rel-16 standard of 3GPP based on 5G technology [32].…”
Section: Related Workmentioning
confidence: 99%
“…The C-V2X has been standardised by the 3GPP in Release 14 [ 7 , 31 ]. The lower layers of C-V2X are specified by the 3GPP for radio access, whereas the upper layers (i.e., applications, facilities, networking, transport and security) are reused from the ETSI C-ITS and DSRC standards.…”
Section: Related Workmentioning
confidence: 99%
“…With the emergence of 5G, the use of cellular V2X (C-V2X) [ 6 , 7 ] is gaining more attention worldwide through the execution of promising trials of vehicular services [ 8 , 9 ]. For example, a mobile edge computing (MEC) infrastructure was deployed in Germany [ 10 ] along 30 km of the A9 motorway, where it was demonstrated that the vehicles can exchange information with an end-to-end latency below 20 ms using LTE.…”
Section: Introductionmentioning
confidence: 99%
“…T HE The Internet of Vehicles (IoV) has emerged as a new paradigm driven by the innovations in vehicular communications. In the IoV concept, vehicles are equipped with sensors, control and computing units, communication, storage, and learning capabilities, which allows the integration of smart vehicles with the Internet, transport infrastructure and other road users via vehicle-to-everything (V2X) communications [1], [2]. During long time, the only V2X solution was the dedicated short-range communication (DSRC), which is based on the IEEE 802.11.…”
Section: Introductionmentioning
confidence: 99%